Short‐term protein restriction at advanced age stimulates FGF21 signalling, energy expenditure and browning of white adipose tissue. (9th November 2020) - Dommerholt, Marleen B.; Blankestijn, Maaike; Vieira‐Lara, Marcel A.; van Dijk, Theo H.; Wolters, Henk; Koster, Mirjam H.; Gerding, Albert; van Os, Ronald P.; Bloks, Vincent W.; Bakker, Barbara M.; Kruit, Janine K.; Jonker, Johan W.
Abstract : Dietary protein restriction has been demonstrated to improve metabolic health under various conditions. However, the relevance of ageing and age‐related decline in metabolic flexibility on the effects of dietary protein restriction has not been addressed. Therefore, we investigated the effect of short‐term dietary protein restriction on metabolic health in young and aged mice. Young adult (3 months old) and aged (18 months old) C57Bl/6J mice were subjected to a 3‐month dietary protein restriction. Outcome parameters included fibroblast growth factor 21 (FGF21) levels, muscle strength, glucose tolerance, energy expenditure (EE) and transcriptomics of brown and white adipose tissue (WAT). Here, we report that a low‐protein diet had beneficial effects in aged mice by reducing some aspects of age‐related metabolic decline. These effects were characterized by increased plasma levels of FGF21, browning of subcutaneous WAT, increased body temperature and EE, while no changes were observed in glucose homeostasis and insulin sensitivity. Moreover, the low‐protein diet used in this study was well‐tolerated in aged mice indicated by the absence of adverse effects on body weight, locomotor activity and muscle performance. In conclusion, our study demonstrates that a short‐term reduction in dietary protein intake can impact age‐related metabolic health alongside increased FGF21 signalling, without negatively affecting muscle function. These findings highlight the potential of protein restriction as a strategy to induce EE and browning of WAT in aged individuals. Abstract : A reduced dietary protein intake has been demonstrated to improve metabolic health under various conditions. Here, it is shown that a short‐term 7% low‐protein dietary intervention can impact age‐related metabolic health in 18‐month‐old animals. Alongside increased plasma fibroblast growth factor 21 levels, a low‐protein diet induces energy expenditure and browning of white adipose tissue in 18‐month‐old mice, without negatively affecting muscle strength.